(untitled) (CHORNOMORSKI BOTANICAL JOURNAL, 2024)
The importance of soil algae for soil restoration is elucidated. The systematic and ecological structure of algae-flora on arboreal plantings in the revegetated coal dump of mine Svyato – Serafimivs’ka (Donetsky region) is studied. The dominant species of algae coenoses and Jakkar index is determined. A checklist of soil algae-flora is is made that includes 30 species from five divisions: Cyanophyta – 2 sp. (7%), Chlorophyta – 22 (73%), Xanthophyta – 1 (3%), Bacillariophyta – 3 (10%), Eustigmatophyta – 2 (7%).